The Process of Chinese Students’ Cross-cultural Adaptation and Their Main Difficulties Encountered while Studying in the Upper Northern Thai Universities - Sun, Kang; Yossuck, Pradtana; Panyadee, Chalermchai; Ek-lem, Bongkochmas (Humanities, Arts and Social Sciences Studies, 2020)
Increasingly, more students have chosen to study for their degree in upper northern Thailand since the government of China implemented new policies of opening up in the field of education in recent years. However, Chinese students’ cross-cultural adaptation process has become an important factor affecting their academic achievements. The aim of this research is to investigate the Chinese students’ performance in four fields (social-cultural, academic, environmental and psychological field) of cross-cultural adaptation. In addition, it identifies the main difficulties Chinese students encountered during their time at the upper northern Thai universities. The selected sample size was 314 students from the eight upper northern Thai universities. In-depth interviews, focus group discussions and structured questionnaires were used for data collection. The data analysis method for determining the main difficulties was multiple regression. The results of the research showed: a) Chinese students’ cross-cultural adaptation process was roughly in a shape of “U-Curve”, furthermore, different Chinese students group performed differently in the four fields of cross-cultural adaptation; b) Eleven main difficulties were found to be contributing factors affecting the process of Chinese students’ cross-cultural adaptation, among which ‘being not accustomed to campus life’, ‘having difficulty in understanding courses’, ‘not having good job prospects’, and ‘having difficulty in fitting-in with Thai society’ were the most influential items. Finally, some useful suggestions for both Chinese students and Thai universities were put forward to help these students to become better adapted to the host Thai environment.